Konsep Pendidikan Perspektif Ivan Illich dan Arthur Schopenhauer - Niken Ristianah; Toha Ma’sum (Darajat: Jurnal Pendidikan Agama Islam, 2021)
Education for human life is an absolute necessity that must be fulfilled throughout life, the purpose of life will be realized. The purpose of education is to form a complete human being in the sense of developing individual potentials in a harmonious, balanced, and integrated manner. Achieving the above objectives, education uses a system or component that will carry out a function to support the achievement of goals. These components are interconnected with each other, influence each other, and need each other. These components are related to several elements that must exist in education, both elements of input, process, and elements of results (outcomes). In addition, education as a whole is also related to efforts to empower the potential possessed by humans both physically, spiritually, intellectually, spiritually, emotionally, socially and culturally as well as various potentials possessed by humans.